A Viper bite in an urban area A case report - EFEOĞLU, MELİS; DENİZBAŞI ALTINOK, ARZU (My University, 2022)
Envenomous viper snakes are not natural inhabitants of Istanbul, Turkey. The city is crowded and lacks an appropriate area for wild life. Viper snakes are mostly found in southern and middle rural Anatolia in Turkey. To our knowledge, viper bites have not been reported in our urban area previously. Here, we report a envenomous snakebite case, treated with polyvalent antivenom successfully. The snake was identified as Vipera Pontica, by the National Poisons Center.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Viper; Snakebite; Venoms; Antivenins; SNAKEBITES; ANTIVENOM; Viper; Snakebite; Venoms; Antivenins